2008
DOI: 10.1089/thy.2007.0148
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Same Day Discharge in Patients Undergoing Sutureless Thyroidectomy: A Comparison of Local and General Anesthesia

Abstract: The electrothermal bipolar vessel sealing system permits safe, same day discharge in patients undergoing thyroid surgery with a low complication rate irrespective of the type of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 20 publications
0
72
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] In the UK, the British Association of Day Surgery included thyroidectomy as a potential day-case procedure in 2001 but the 2011 consensus statement of the British Association of Endocrine and Thyroid Surgeons (BAETS) was more cautious, recommending that thyroidectomy should be a 'day-and-stay' procedure with a minimum length of stay of 23 hours. 22 This study examined the pattern and timing of post-thyroidectomy haemorrhage in a large interdisciplinary district hospital to identify potential risk factors for this complication as well as the extent to which its impact on preventing short stay thyroid surgery may be mitigated.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] In the UK, the British Association of Day Surgery included thyroidectomy as a potential day-case procedure in 2001 but the 2011 consensus statement of the British Association of Endocrine and Thyroid Surgeons (BAETS) was more cautious, recommending that thyroidectomy should be a 'day-and-stay' procedure with a minimum length of stay of 23 hours. 22 This study examined the pattern and timing of post-thyroidectomy haemorrhage in a large interdisciplinary district hospital to identify potential risk factors for this complication as well as the extent to which its impact on preventing short stay thyroid surgery may be mitigated.…”
mentioning
confidence: 99%
“…Five studies (6,15,17,19,21) comprising 1,717 cases identified the proportion of outpatients with a transient RLN injury and reported results ranged from 0-4% (6,15). Only one study by Snyder et al (6) reported on inpatient and outpatient results (Figure 3).…”
Section: Transient Recurrent Laryngeal Nerve (Rln) Injurymentioning
confidence: 99%
“…Ten studies comprising 2,505 cases reported on permanent RLN injury in OPS cases (5,6,8,13,15,(17)(18)(19)21), with rates ranging from 0-2% (13,18,19). There were 11 reported cases (0.4%) of vocal cord paralysis.…”
Section: Permanent Rln Injurymentioning
confidence: 99%
See 2 more Smart Citations